Q) Find the ratio in which the line segment joining the points (5, 3) and (–1, 6) is divided by Y-axis.

Ans: 

Method 1:

Step 1:  By section formula, coordinates of point P (X, Y) which lies between two points (x1, y1), (x2, y2) will be given by:

P (X,Y) = (\frac{m_1 \times_2 + m_2 \times_1}{m_1 + m_2}, \frac{m_1 Y_2 + m_2 Y_1}{m_1 + m_2})

here, the point divides the line in the ratio of m1 : m2

Step 2:  Now if the given points A (5, 3) and B(- 1, 6) are divided in the ratio of m : n, then:

coordinates of dividing point (x, y) = (\frac{m (- 1) + n (5)}{m + n}, \frac{m (6) + n (3)}{m + n})

= (\frac{(- m + 5 n)}{m + n}, \frac{(6 m + 3 n)}{m + n})

Step 3:  Next, since this point lies on line Y axis, it means x = 0, this point will satisfy the equation

\frac{(- m + 5 n)}{m + n} = 0

∴ – m + 5 n = 0

∴ m = 5 n

∴ m : n = 5 : 1

Therefore, the line segment divides the line in ratio of 5:1.

Method 2: if we plot the given points and connect them: Find the ratio in which the line segment joining the points (5, 3) and (–1, 6) is divided by Y-axis.

Let’s make an equation of the line passing through points A and B:
y – Y1 = \frac{Y_2 - Y_1}{\times_2 - \times_1} (x – X1)
y – 3 = \frac{(6-3)}{(-1 -5)} (x – 5)
y – 3 = \frac{3}{- 6} (x – 5)
y – 3 = \frac{1}{- 2} (x – 5)
– 2 (y – 3) = (x – 5)
– 2 y + 6 = x – 5
x + 2y – 11 = 0

Since, at Y-axis, x = 0, ∴ y = \frac{11}{2} = 5.5
Hence, the line x + 2y – 11 = 0, intersects Y -axis at (0, 5.5). 
Let’s say this is point C.

Now, Distance between point A (5,3) and C (0, 5.5)
= \sqrt{(- 5)^2 + (5.5 - 3)^2}
= \sqrt{25 + 6.25}
= \sqrt{31.25}

Now, Distance between point B (-1,6) and C (0, 5.5)
= \sqrt{(-1)^2 + (6-5.5)^2}
= \sqrt{1 + 0.25}
= \sqrt{1.25}

Now, Ratio between AC/ BC = \frac{\sqrt{31.25}}{\sqrt{1.25}}
= \sqrt{\frac{31.25}{1.25}
= \sqrt{\frac{3125}{125}
= \sqrt{\frac{125}{5}
= \sqrt{\frac{25}{1}
= \frac{5}{1}

Therefore, m:n = 5:1

How to check your answer:

Here, Let’s consider that the ratio of m:n = 5:1. Hence, the coordinates of the intersection point are: = (\frac{(- m + 5 n)}{m + n}, \frac{(6 m + 3 n)}{m + n}) = (\frac{(- 5 + 5 (1))}{5 + 1}, \frac{(6 (5) + 3 (1))}{5 + 1}) = (0, \frac{33}{6}) = (0, 5.5)

Since this point lies on the line y – axis, where x = 0. We can see that this is true for our coordinates of the intersection point, hence our answer is correct.

Please press the “Heart” button, if you like the solution.

Leave a Comment

Your email address will not be published. Required fields are marked *

Scroll to Top